Pemberian Sanksi Kasepekang dalam Sengketa Tanah Pekarangan Desa di Banja Bedil, Desa Adat Baha, Kecamatan Mengwi, Kabupaten Badung Provinsi Bali - I Kadek Ambara Putra; I Made Suwitra; Diah Gayatri Sudibya (Warmadewa Press, 2024)
The Kasepekang sanction in customary land disputes is one of the customary sanctions in Bali. Kasepekang means temporary dismissal as a Village citizen, kasepekang is interpreted as permanent or permanent dismissal regulated by Bali Provincial Regulation No. 4 of 2019 related to Customary Villages. This research was conducted with the aim of describing to find out how the Tenure of Rights over Village Land in Banjar Bedil, Baha Customary Village, Mengwi District, Badung Regency, Bali Province and to find out how the Procedure for Giving Kasepekang Sanctions in Disputes over Tenure over Village Land in Banjar Bedil, Baha Customary Village, Mengwi District, Badung Regency, Bali Province. This research utilizes empirical-based legal research methods. The results of this study indicate that there is ownership of certificates for private control where the custom cannot claim that the land is customary land where the certificate is a strong evidence, namely as a physical statement of land ownership.